Pengaruh Indeks Global, Harga Minyak Dunia dan Variabel Makroekonomi terhadap Indeks Harga Saham Jakarta Islamic Index (JII) - Feri Sukma Putra; Rusdi Hidayat N (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
Indonesia is the country with the largest muslim population in the world, so information related to sharia stock indexes has a fairly important role to understand capital market dynamics and investment decisions. This research aims to find out the simultaneous and partial influence of the Dow Jones Industrial Average, World Oil Prices, BI 7-Day reverse Repo Rate and Inflation on the Jakarta Islamic Index stock index on the Indonesia Stock Exchange. This study uses a type of skunder data in the form of historical records of reports per end of the month of the index obtained from the official financial website, namely Bank Indonesia, Investing and the Indonesia Stock Exchange. The population in this study is a time-series data of 60 months, starting from September 2016 to August 2021 with a sample determination technique using the saturated sample method. Data is tested and analyzed using multiple linear regression analysis techniques. Hypotheses are tested using the F test and the t test. The results of the analysis showed that simultaneously variable Dow Jones Industral Average (DJIA), World Oil Price, BI 7-Day reverse Repo Rate and Inflation had a significant effect on the Jakarta Islamic Index (JII) Stock Index on the Indonesia Stock Exchange (IDX). Partially DJIA and BI 7-Day reverse Repo Rate negative but not significant, while World Oil Price and Inflation have a significant positive effect on the Jakarta Islamic Index (JII).